Effects of Pretilachlor Herbicide on the Embryos and Adults of Javanese Medaka (Oryzias javanicus) - Khairi, Engku Ahmad; Mazlan, Norida; Asib, Norhayu; Hafezul, Wan Mohd; Ghani, Wan Abdul (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 4DO - 10.25073/2588-1094/vnuees.5272, 2025)
Pretilachlor (PRT), a commonly used herbicide in Malaysian rice fields, poses environmental concerns due to its potential impact on other living organisms. In this study, Javanese medaka ( Oryzias javanicus ) were used as a model organism to evaluate the effects of PRT on the embryo development and oxidative stress on adult species. Water samples from the rice fields that were treated with PRT were collected at four time points: 14 days before planting (DBP), 14, 42, and 70 days after planting (DAP). These samples provided a basis for preparing four different concentrations of PRT (0.040 mg/L, 0.045 mg/L, 0.050 mg/L, and 0.055 mg/L) for exposure experiments. Embryos exposed to these PRT concentrations exhibited teratogenic responses, including reduced hatchability and increased heart rates, even at the lowest concentration of 0.04 mg/L. The adverse effects were more pronounced at higher concentrations, with mortality rates reaching 60-70%. Observations revealed significant developmental disruptions, including early hatching and prolonged attachment to the yolk sac, which hindered the fry's ability to swim normally. These defects highlight the potential for PRT to cause substantial harm to aquatic life. In addition to embryo studies, adult Javanese medaka were also exposed to similar PRT concentrations. The results indicated that higher PRT levels led to increased oxidative stress, as evidenced by elevated metallothionein (MT) levels. Despite the increased stress, no mortality was observed in adult fish, suggesting that while PRT exposure is harmful, it may not be immediately lethal to adults. This study underscores the ecological risks associated with the use of PRT in agriculture, particularly its potential to contaminate water bodies and affect aquatic organisms. Continuous monitoring of PRT residues in local rice fields is crucial to ensure its regulated usage. The findings advocate stringent controls to mitigate the long-term ecological impacts of PRT, promoting safer agricultural practices to protect the aquatic environment.